Citizen and Community Science Approaches to Understanding Changes in Coastal Habitats Using Anecdata.org - Garretson, Alexis; Bailey, Cait; Taylor, Ashley; Dabulewicz, Alexis; Bisson, Beth; Dorn, Nathan; Kaczor, K.; Nahf, Mary; Webber, Hannah; Whiting, Mark; Disney, Jane (Maine Policy Review, 2023)
Coastal ecosystems are facing increasing threats from human activities and environmental changes. Climate change, in particular, presents challenges for policymaking as it is causing significant changes to the oceans and coastlines, with social, economic, and environmental impacts on coastal communities. However, there is often a lack of data at the appropriate scales to address these concerns. Online tools that support the collection of citizen science and community science data can provide stakeholders and policymakers with a wealth of information and data on ocean-related topics, such as water quality, marine biodiversity, and ocean health. Citizen science platforms, like Anecdata.org, can facilitate data collection, raise public awareness, and encourage the engagement of stakeholders in ocean policymaking. Anecdata.org is a citizen science platform developed in Maine that supports data collection and project management for coastal conservation efforts worldwide. This community-driven platform promotes effective, open, and democratized science, hosting numerous active projects with users who are helping to address critical coastal issues. Here, we review Maine coastal projects on the Anecdata platform, examine the environmental trends highlighted in these projects, and discuss how citizen science data can play a role in coastal decision-making. These case studies will demonstrate the utility of citizen and community science approaches to monitoring Maine coastal ecosystems, understanding and predicting the impacts of climate change, and informing policymaking for coastal conservation. Taken together, these projects provide diverse, critically important data as well as a meaningful way for individuals and communities to engage in protecting and preserving Maine’s iconic coastal resources.